Lived experience of recurrent miscarriage: women and their partners’ experience of subsequent pregnancy and support within an NHS specialist clinic – a qualitative study - Debra Bick; Bronwyn Harris; Siobhan Quenby; Amelia Hawkes; Rebecca Claire Shields; Jo Parsons (BMJ Open, 2023)
Objective This study aims to describe the lived experiences of couples with a history of recurrent miscarriage in subsequent pregnancies and their perception of clinic support and cytogenetic investigations.Design A qualitative interview study with a phenomenological approach. Semistructured interviews were conducted using video conferencing software. Two researchers coded the transcripts and developed themes.Setting A National Health Service (NHS) hospital in central England between May 2021 and July 2021, during the COVID-19 pandemic.Participants Patients attending a specialist recurrent miscarriage clinic and their partners. This clinic accepts referrals from all over the UK for couples who have suffered two or more miscarriages.Results Seventeen participants were interviewed: 14 women and 3 male partners. Six main themes were identified from the data. Three related to the women’s lived experience of recurrent miscarriage (emotions in pregnancy, confidence in their bodies, expectations and coping strategies) and three related to the clinical support offered by the NHS service (impact of early pregnancy scanning, effect of the COVID-19 pandemic and cytogenetic investigations).Conclusions Pregnancy following recurrent miscarriage is extremely difficult. Recurrent miscarriage specialist services can provide couples with support and access to early pregnancy scanning, which can make the first trimester of pregnancy manageable. Partners should not be excluded from the clinic as it can result in a feeling of disconnect. Cytogenetic testing of pregnancy tissue can offer couples with recurrent miscarriage closure after pregnancy loss and is a desired investigation.